Novel insights into the neuroendocrine control of inflammation: the role of GR and PARP1 - Aprile García, Fernando (2013)
Inflammatory responses are elicited after injury, involving release of inflammatory mediators that ultimately lead, at the molecular level, to the activation of specific transcription factors (TFs; mainly activator protein 1 and nuclear factor-kB). These TFs propagate inflammation by inducing the expression of cytokines and chemokines. The neuroendocrine system has a determinant role in the maintenance of homeostasis, to avoid exacerbated inflammatory responses. Glucocorticoids (GCs) are the key neuroendocrine regulators of the inflammatory response. In this study, we describe the molecular mechanisms involved in the interplay between inflammatory cytokines, the neuroendocrine axis and GCs necessary for the control of inflammation. Targeting and modulation of the glucocorticoid receptor (GR) and its activity is a common therapeutic strategy to reduce pathological signaling. Poly (ADP-ribose)polymerase 1 (PARP1) is an enzyme that catalyzes the addition of PAR on target proteins,a post-translational modification termed PARylation. PARP1 has a central role in transcriptional regulation of inflammatory mediators, both in neuroendocrine tumors and in CNS cells. It is also involved in modulation of several nuclear receptors. Therefore, PARP1 and GR share common inflammatory pathways with antagonic roles in the control of inflammatory processes, which are crucial for the effective maintenance of homeostasis.